Critical accumulation of fertilizer-derived uranium in Icelandic grassland Andosol - Sun, Yajie; Amelung, Wulf; Gudmundsson, Thorstein; Wu, Bei; Bol, Roland (Environmental Sciences Europe, 2020)
Long-term phosphorus (P) fertilizer application can lead to an accumulation of uranium (U) in agricultural soil, potentially posing risks on the environment and human health. In this study, we found that such risks could be severe in two long-term grasslands (Andosol) in Iceland (Sámstaðir and Geitasandur) after about 50 years of P fertilization. At Sámstaðir, where P fertilizers were applied at an annual rate of 39.3 kg ha−1 year−1, the soil U concentration increased from 0.65 mg kg−1 in the unfertilized soil to 6.9 mg kg−1 in the fertilized surface soil (0–5 cm). At Geitasandur with P fertilization rate at 78.6 kg ha−1 year−1, the soil U concentration reached 15 mg kg−1. The average annual U accumulation rates were 130 and 310 µg kg−1 year−1, respectively. These values were larger, by up to a factor of ten, than any previously reported rates of fertilizer-derived U accumulation. However, the U concentration in one of the applied P fertilizers was 95 mg U kg−1 fertilizer, similar to the median value of those reported in previous studies, and thus unlikely to be the only factor leading to the high U accumulation rates. By contrast, as our Andosols had low bulk density within a range of 0.2 to 0.5 g cm−3, the annual U inputs to the 0–5 cm soil were 19 g ha−1 year−1 and 32 g ha−1 year−1 at the two sites, respectively, within the range of to-date reported values in agricultural systems. In addition, we found that U was mostly retained in the surface soil rather than mobilizing to deeper soil. This was likely due to the fact that the Andosols were rich in organic matter which promoted U retention. Therefore, the observed high U accumulation rates were a result of the combination of (i) the large amounts of the applied P fertilizers and (ii) the soil properties of the Andosols with low bulk density and elevated organic matter content concentrating U in the upper surface soil. Our study shows that agricultural production systems on Andosols may have already suffered from severe U contamination due to P fertilization. ...